Cytomegalovirus seropositivity is associated with reduced risk of multiple sclerosis—a presymptomatic case–control study. (27th June 2021) - Grut, Viktor; Biström, Martin; Salzer, Jonatan; Stridh, Pernilla; Jons, Daniel; Gustafsson, Rasmus; Fogdell‐Hahn, Anna; Huang, Jesse; Brenner, Nicole; Butt, Julia; Bender, Noemi; Lindam, Anna; et al.
Abstract: Background and purpose: Epstein–Barr virus (EBV) and human herpesvirus 6A (HHV‐6A) are associated with increased risk of multiple sclerosis (MS). Conversely, infection with cytomegalovirus (CMV) has been suggested to reduce the risk of MS but supporting data from presymptomatic studies are lacking. Here, it was sought to increase the understanding of CMV in MS aetiology. Methods: A nested case–control study was performed with presymptomatically collected blood samples identified through crosslinkage of MS registries and Swedish biobanks. Serological antibody response against CMV, EBV and HHV‐6A was determined using a bead‐based multiplex assay. Odds ratio (OR) with 95% confidence interval (CI) for CMV seropositivity as a risk factor for MS was calculated by conditional logistic regression and adjusted for EBV and HHV‐6A seropositivity. Potential interactions on the additive scale were analysed by calculating the attributable proportion due to interaction (AP). Results: Serum samples from 670 pairs of matched cases and controls were included. CMV seropositivity was associated with a reduced risk for MS (OR = 0.70, 95% CI 0.56–0.88, p  = 0.003). Statistical interactions on the additive scale were observed between seronegativity for CMV and seropositivity against HHV‐6A (AP 0.34, 95% CI 0.06–0.61) and EBV antigen EBNA‐1 (amino acid 385–420) at age 20–39 years (AP 0.37, 95% CI 0.09–0.65). Conclusions: Cytomegalovirus seropositivity is associated with a decreased risk for MS. The protective role for CMV infection in MS aetiology is further supported by the interactions between CMV seronegativity and EBV and HHV‐6A seropositivity. Abstract : The association of cytomegalovirus and multiple sclerosis was assessed in a case–control study of presymptomatically collected samples. Cytomegalovirus seropositivity was found to reduce the risk of developing multiple sclerosis by 30%. Interactions between cytomegalovirus, Epstein–Barr virus and human herpesvirus 6A serostatus further impact the risk of multiple sclerosis.